Analisis Penawaran Tenaga Kerja Perempuan Pada Industri Tenun di Kecamatan Klungkung Kabupaten Klungkung - Pertiwi, Nyoman Reva; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 8. Agustus 2017(pp.1395-1627), 2017)
Labor Supply in weaving industry at Klungkung District had fluctuation caused by any factors, suchs as competition, similar products manufactured, until there is no more new generation.  The wages offered in this industry relatively high, but the owner of the weaving industry still shortage of weavers and new generation. The wages offered in this industry is relatively high, but businesses weaving industry have not craftsmen and future generations. The purpose of this study are to analyze the influence of age, education level and rationality on the probability of female labor in performing the labor supply remains in the weaving industry. Tthis study use logistic regression analysi method. The results this study are the employment of older and higher rationality have higher probability to do the labor supply of remain in the weaving industry. The level of education has no effect on labor supply of women, then workers who have higher levels of education have a lower probability to perform labor supply remains in the weaving industry.
Keywords: usia, tingkat pendidikan, rasionalitas, penawaran tenaga kerja perempuan